2020
DOI: 10.9734/ajfar/2020/v6i430105
|View full text |Cite
|
Sign up to set email alerts
|

Ulvan as A New Trend in Agriculture, Food Processing and Medicine

Abstract: In this work the researcher is looking for natural, new, safe, cheap and available compounds that can be used as antimicrobial and antioxidant in the medical and agricultural fields. A sulfated polysaccharide, Ulvan was extracted from Ulva lactuca and purified by cold or hot water-extraction and ethanol-precipitation with yield = 5:10% (w-w). Its appearance and touch like gel. Characterization of active groups of Ulvan was achieved by FT-IR spectroscopy, its content of sulfate = 3.998% (w-w) was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…From FTIR-ATR of bio-nanocomposite films and FT-IR of ulvan was indicated that Ag-NPs is a good electrophile and react with nucleophile oxygen of both hydroxyl, carboxyl and sulfate groups of ulvan. Finally, FTIR-ATR should indicate the interaction between sulfated polysaccharides ulvan and biosynthesized silver nanoparticles through the functional groups of ulvan and indicated also the success of bio-nanocomposite films formation (Moura et al, 2012); (Amin, 2020b). Films Appearance (Fig.…”
Section: Ft-ir Spectra Of Ulvan and Ftir-atr Of Bio-nanocomposite Filmentioning
confidence: 98%
See 4 more Smart Citations
“…From FTIR-ATR of bio-nanocomposite films and FT-IR of ulvan was indicated that Ag-NPs is a good electrophile and react with nucleophile oxygen of both hydroxyl, carboxyl and sulfate groups of ulvan. Finally, FTIR-ATR should indicate the interaction between sulfated polysaccharides ulvan and biosynthesized silver nanoparticles through the functional groups of ulvan and indicated also the success of bio-nanocomposite films formation (Moura et al, 2012); (Amin, 2020b). Films Appearance (Fig.…”
Section: Ft-ir Spectra Of Ulvan and Ftir-atr Of Bio-nanocomposite Filmentioning
confidence: 98%
“…The yield of polysaccharide (%) was calculated by the following equation as described in (Amin, 2020b) and (Shalaby and Amin 2019):…”
Section: Extraction Of Ulvan Polysaccharide From U Lactucamentioning
confidence: 99%
See 3 more Smart Citations